Using TRIM-SRIM code simulations to determine defect density produced in HOPG irradiated with high energy heavy ions. Issue 1 (1st September 2022) - Avanzi, L.H.; Aguiar, V.A.P.; Costa, K.M.; Santarelli, T.O.; Medina, N.H.; Oliveira, J.R.B.; Cappuzzello, F.; Iazzi, F.; Capirossi, V.; Pinna, F.; Cavallaro, M.; Guazzelli, M.A.; et al.
Abstract: This work is part of the NUMEN Project (NUclear Matrix Elements for Neutrinoless double beta decay), which, among other goals, aims to measure cross-section of double charge exchange reactions (DCE). In the experiments to be carried out at the Laboratori Nazionali del Sud, in Catania, Italy, a target deposited on a carefully chosen backing (substrate) will be irradiated with a high energy ion beam and, importantly, neither the target nor the substrate will be allowed to overheat as this would affect their structures and its properties, which are special for the experiment. Within this context, highly oriented pyrolytic graphite (HOPG) was chosen as a substrate for the deposition of target elements that will be irradiated by ions such as 12 C, 18 O and 20 Ne, with energies ranging from 15 MeV/u to 60 MeV/u. HOPG is considered a semimetal structured in layers, being composed of a stack of graphene sheets with a small and very subtle disorientation (less than 1°), which makes it to approach to a single crystal. With its specific flat hexagonal molecular structure, consisting only of carbon atoms, HOPG has good thermal conductivity in these sheets, making it an excellent candidate as a heat sink. However, for the HOPG to act with thermal energy dissipation functionality during the experiments proposed by the NUMEN project, it is necessary to verify whether possible changes caused by exposure to the radiation beam have a direct or indirect influence on its mechanical and thermal properties. Regarding the thermal conductivity, vacancies produced during irradiation is one of the factors that considerably decrease such property. As the production of vacancies during irradiation is one of the factors that considerably decrease thermal conductivity, in this work it was used the SRIM/TRIM code simulations to investigate the mechanisms of vacancy production in the target plus HOPG backing system. In the simulations, it was considered different types and doses of incident ion beams as well as different target thickness. From the results it was possible to estimated how long a target-HOPG system can be irradiated before the HOPG high heat conductivity property is lost.